Responsible film censorship and classifications at the advent of Industrial Revolution 4.0 - Jessica, Sim (International Journal of Psychosocial Rehabilitation, 2020)
Responsible film censorship in Malaysia is putting in place appropriate socio-political guidelines which will do away with outdated practices but liberate its control for producers and distributors without jeopardizing the nation’s security. The study is guided by these objectives: i. How are the Malaysian film censorship practices relevant in the present context? ii. How film classification helps to manage censorship issues? iii. How technical innovations to censorship practices satisfy stakeholders’ expectations? The study adopted the qualitative paradigm to research this study. Data was gathered through extensive in-depth interviews of censor board officers, audience, film distributors and producers. Content analysis of films successful and banned were conducted. The study arrived at several conclusions: 1. LPF is concerned for the national security and peace of the nation. Any practice or content that goes counter to the sensitivities and preservation of value and cultural traditions (violence among youths) of the people of Malaysia, becomes irrelevant; 2. Stakeholders’ expectations of compliance and lenience have always been met with frequent and close consultations to issue arising pertaining to guidelines and film classifications; 3. For the LPF to stay relevant to the expectations of the nation and the stakeholders, the censorship board has stepped up its initiatives under their media literacy program to drop ineffective practices and enhance interventions for officers and stakeholders.